RISK FACTORS OF BREAST CANCER AMONG WOMEN IN AKOKO SOUTH WEST LOCAL GOVERNMENT AREA OF ONDO STATE - BABATUNDE, OBALASE, STEPHEN; BOLANLE, OGBEYE GBEMISOLA; CLEMENT, ADELUSI; OMOTOLA, ADELUSI RACHAEL (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The current study was designed to investigate the risk factors of breast cancer among womenin Akoko South West Local Government Area of Ondo state. Questionnaire was the researchinstrument. Two research questions and two hypotheses were raised in the study. Data were gatheredusing a questionnaire which was subjected to face and content validity by expert in education. Thereliability value of Pearson product moment correlation was 0.93 which indicated that the instrumentwas reliable before it was administered on the respondents. The study involved 200 respondentswhich were randomly selected. Data collected from the respondents were subjected to statisticalanalysis using simple percentage, chi-Square and correlation. Analysis of the data revealed thatSocio – Economic Cultural and Demographic factors such as age, travel distance to screeningfacility, cost of screening, most cultural practices and socio – commitments have significant negativecorrelation with breast cancer screening uptake. However, marital status, educational level, socio –economic status, most religious practices and socio – cultural factors have a significant positiveassociation with breast cancer screening uptake. Psychosocial variables such as fear, anticipatedpain and discomfort, stigma and concern for embarrassment were found to be significantlyassociated to breast cancer screening uptake among the respondents. Institutional characteristicssuch as Breast Health Education, guidance and follow up by nurses on Breast ScreeningExamination, psychological care by the psychologist. Advertisements on breast cancer and screeninghave significant and positive correlation with breast cancer screening uptake.